A 3-D model for simulation of weak interface slippage for fracture height containment in shale reservoirs. (July 2018) - Tang, Jizhou; Wu, Kan
Abstract: Shale formations often consist of multiple distinct layers with varying rock properties, in-situ stress states, and interface properties between layers. Weak horizontal interfaces often affect fracture height growth and induced complex fracture geometry. In this paper, a fully three-dimensional displacement discontinuity method is developed to investigate slippage of weak horizontal interfaces and understand the effects of the slippage on fracture height growth. Horizontal fracture segments are regarded as weak horizontal interfaces and vertical fractures would either be arrested or step over interfaces. Results indicate that a width jump of the vertical fracture occurs at the crossing position of the horizontal interface, as a result of shear displacement discontinuities along the horizontal fracture segment. The width jump hinders the vertical fracture growth in the height direction, which is regarded as a new mechanism of fracture height containment. Shear displacement discontinuities and width jump increase with the increment of the distance between the center of the vertical fracture and horizontal fracture segment. The larger the width jump, the more difficult the vertical fracture continues to propagate in the height direction, which implies that the vertical fracture tends to be arrested by the interface when the wellbore is far away from the interface.